Relationship Between Fear of Coronavirus and Life Satisfaction in Geriatric Individuals - Emine Atıcı; Merve Akış; Emine Eda Kurt (Galenos Yayinevi, 2023)
Objective:This study was planned to investigate the relationship between the fear of coronavirus and life satisfaction in geriatric individuals.Materials and Methods:Demographic information form, Coronavirus Fear scale (CFS), and Life Satisfaction scale (LSS) were used as data collection tools. Seventy-nine people over the age of 65 were included in the study.Results:As a result of the study, there was a low level of positive correlation between life satisfaction and fear of coronavirus (p<0.05). The 7% effect of CFS on LSS was statistically significant (F5,504 p=0.022). A one-unit increase in the LSS significantly increased the CFS by 0.210 units statistically significantly (p<0.05).Conclusion:This study conducted at the end of the pandemic shows that the presence of geriatric individuals in life and being physically active in daily life positively affects life satisfaction.